2023
DOI: 10.1111/mec.17100
|View full text |Cite
|
Sign up to set email alerts
|

Holocentric repeat landscapes: From micro‐evolutionary patterns to macro‐evolutionary associations with karyotype evolution

Abstract: Repetitive elements can cause large‐scale chromosomal rearrangements, for example through ectopic recombination, potentially promoting reproductive isolation and speciation. Species with holocentric chromosomes, that lack a localized centromere, might be more likely to retain chromosomal rearrangements that lead to karyotype changes such as fusions and fissions. This is because chromosome segregation during cell division should be less affected than in organisms with a localized centromere. The relationships b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…However, even in our small sample, we also observed considerable differences in genome sizes between and within populations in P. icarus and P. fulgens (Table I). Indeed, study of repeat landscapes in Erebia butterflies showed that repeat composition can vary greatly within species and the variation scales with population divergence (Cornet et al 2023). Further study is needed to confirm whether increase in genome size can be ascribed to activity of horizontally transferred mobile elements (Kandul et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, even in our small sample, we also observed considerable differences in genome sizes between and within populations in P. icarus and P. fulgens (Table I). Indeed, study of repeat landscapes in Erebia butterflies showed that repeat composition can vary greatly within species and the variation scales with population divergence (Cornet et al 2023). Further study is needed to confirm whether increase in genome size can be ascribed to activity of horizontally transferred mobile elements (Kandul et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of repeat DNA— e . g ., LINEs, LTRs, and Helitrons—differ significantly between Carex lineages whose chromosome arrangements evolve at different rates (Cornet et al 2023). Moreover, repeat regions in Carex genomes investigated correlate with chromosome breakpoints across deep phylogenetic breaks as well as within species (Escudero, Marques, Lucek & Hipp 2023, Höök et al 2023), pointing to a mechanism by which natural selection could operate on the genome architecture of chromosome rearrangements in the genus.…”
Section: Discussionmentioning
confidence: 99%
“…S11). Moreover, to assess genome-wide repeat expansion across the major Transposable Element (TE) superfamilies 40 , we used repeat landscapes, which showed a comparable pattern within the Z/W (Fig. 3, S12).…”
Section: The Amborella W Shows Little Degenerationmentioning
confidence: 99%